Fish Assemblage Structure in Al-Huwaizah marsh southern of Iraq after inscribed on the World Heritage List - Al-Thahaibawi, Basim M. Hubain; Younis, Kadhim H.; Al-Mayaly, Ithar K.A. (Iraqi Journal of Science, 2019)
The fish assemblage structure in Al-Huwaizah marsh, southern of Iraq was assessed. Fish samples collected monthly by different fishing means from period December 2017 to November 2018. A total of 28959 individual of fish belonging to 9 families and 19 species were collected, 11 of them of native species and 8 of alienspecies. The numerical dominance index value (D3) of the highest three abundant species comprised 74.26% of the total fish caught, included Planiliza abu (Al-Keshny) 38.2% ; Coptodon zilli (Tilapia red abdomen) 29.41% and Carassius auratus (Prussian carp) 6.65%. The total weight of fish caught 2,190,680 tan, highest weight 312,242kg achieved in July, while lowest weight 41,590 kg found in September. The weight dominance index value (D3) of the highest three species in weight recorded 1,409,973 tan of the total weight of fish caught included C. zilli(Tilapia red abdomen) 659,994 kg , S. triostegus (Jerry fresh water) 495,784 kg and O. aureus (Blue tilapia) 245,195kg.The annual rate value for diversity, richness and evenness indices amounted 1.88, 1.75 and 0.64, respectively. Some of physical and chemical properties were studied such as water temperature which ranged from 11.5°C in January to 31.02°C in August month, dissolved oxygen ranged from 2.24 mg/l in September to 9.9mg/l in February, salinity varied from 1.37‰ in November to 3.76‰ in September and pH which ranged from 7.4 in June to 8.15 in December.Jaccard Similarity Index (Ss%) was used to know the similarity degree between the monthly catch samples. Also associations between distribution of fish species and the environmental variables were quantified by using canonical correspondence analysis (CCA).